STRATEGI PENINGKATAN BED OCCUPANCY RATE RAWAT INAP MATERNAL DENGAN PENDEKATAN KOMUNITAS DI RUMAH SAKIT BAPTIS BATU - Roro Merina Diah Erinurmasari, Raden (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Strategi Peningkatan Bed Occupancy Rate Rawat Inap Maternal Dengan Pendekatan Komunitas Di Rumah Sakit Baptis Batu. One of hospitals indicator to evaluate the effectiveness in inpatient department is calculation of the Bed Occupancy Rate (BOR). Low number of BOR need to be analyzed. This study aimed to analyze the factors causing inefficient BOR. In this qualitative study, author listed problem priorities with USG method, using interviews and focus group discussions to recognize factors that influence BOR, and analyzed data using fishbone analysis. Recommendations were chosen with CARL method and then business model canvas was made to guide the implementation. Some supporting factors were the good teamwork and good maintenance on facilities. Some resisting factors were low of referral from primary health care facilities and knowledge limitation of the referrer primary health care facilities about pregnancy and it risks. The main factor affecting on inefficient BOR in Baptism Batu Hospital was low of referral. Therefore it should be mitigated with community approach.